The Philosophical History of Punishment and Imprisonment - Jonescu, Emil (Curtin University, 2012)
Historically, people have been detained in custodial institutions deemed appropriate no matter how deplorable their conditions. Criminality, considered an illness, was treated by segregated punishment and to varying degrees crime, morality, mental health and religion was deemed somewhat interrelated, Therefore prisons, mental institutions, hospitals and ecclesiastical architecture share philosophical and historical infrastructure. Associated discourse among social reformers established concurrent inter-continental evolutionary threads of 'innovative' proposals, philosophies and architecture specific to incarceration. Conversely, within the West Australian criminal justice system, police lock-ups exist to facilitate temporary detainment of people yet to be proved guilty of an offence. This paper forms the basis of one chapter of my PhD research that discusses the requirements of WA police short-term custodial facilities and calls for contemporary initiatives and a shift in attitudes to acknowledge that dissimilar institutions require different accommodation structures which necessitate a distinctive functional form. Existing deficiencies in specialist literature acknowledging the anomalous complexity of lock-up function indicates constant insufficient consideration of short-term custodial architecture research compared with other institutional typologies that have rapidly spectalised and evolved. Yet social and academic castigation ensure that retrospective adaptive implementation of unrealised conceptions and philosophies remain dismissed and untested.